Human Papilloma Virus 18-Positive Submucosal Small Cell Neuroendocrine Carcinoma of the Vagina: An Immunohistochemical and Genomic Study. (December 2021) - Kitazono, Ikumi; Akahane, Toshiaki; Sakihama, Mika; Yanazume, Shintaro; Matsushita, Michiko; Tabata, Kazuhiro; Kobayashi, Yusuke; Kobayashi, Hiroaki; Umekita, Yoshihisa; Tanimoto, Akihide
Primary vaginal neuroendocrine carcinoma (NEC) is extremely rare among female genital tract tumors. Here, we report 2 cases of vaginal small cell NEC (SCNEC) using immunohistochemistry and next-generation sequencing (NGS) analysis. The 2 patients were in their mid-to-late 70s, presented with abnormal vaginal bleeding and had a vaginal submucosal mass. The biopsied or resected tumors showed a typical neuroendocrine morphology consisting of solid nests of atypical tumor cells, with no specific organoid patterns, and proliferating in the vaginal submucosa. Immunohistochemical analysis showed strong and diffuse expression of chromogranin A, synaptophysin, and p16, but no thyroid transcription factor 1 expression. Additionally, both cases were positive for human papillomavirus (HPV) 18. An NGS-based cancer panel analysis revealed that the tumors carried NF1 and AR mutations, but no major driver mutations were detected. The results of this study suggested that HPV18 infection is linked to vaginal SCNEC.